Examining progress toward the UNAIDS 90-90-90 framework among men who have sex with men, San Francisco, 2014. Issue 9 (1st September 2016) - Raymond, H. Fisher; Scheer, Susan; Santos, Glenn-Milo; McFarland, Willi
ABSTRACT: The Joint United Nations Programme on HIV/AIDS (UNAIDS) has published treatment goals toward ending the HIV epidemic. The worldwide goals are 90% of HIV-infected individuals diagnosed, 90% of those diagnosed taking anti-retroviral treatment and 90% of those on anti-retroviral treatment virally suppressed. In light of the UNAIDS goals and that five years have passed since the adoption of early HIV treatment, we examined the progress toward the 90-90-90 indicators among men who have sex with men (MSM) in San Francisco in 2014. Our data suggest that overall MSM have not yet reached the 90-90-90 goals. Our data also suggest that Black and Latino MSM are further from the goals than White MSM.